Insertion/Deletion markers for assessing the genetic variation and the spatial genetic structure of Tunisian Brachypodium hybridum populations - Neji, Mohamed; Geuna, Filippo; Gordon, Sean P.; Taamalli, Wael; Vogel, John P.; Ibrahim, Yosra; Smaoui, Abd Errazak; Abdelly, Chedly; Gandour, Mhemmed (Recent Research in Science and Technology, 2016)
The wild annual grass Brachypodium hybridum, an allotetraploid species derived from the natural hybridization between the diploid species B. distachyon (2n=10) and B. stacei (2n=20). This trio of species has been suggested as a model system for polyploidy. Brachypodium hybridum is the most widespread Brachypodium species in Tunisia. Natural diversity can be used as a powerful tool to uncover gene function and, in the case of B. hybridum, to understand the functional consequences of polyploidy. Here, we examined the spatial distribution of genetic variation of B. hybridum across its entire range in Tunisia and tested underlying factors that shaped its genetic variation. Population genetic analyses were conducted on 145 individuals from 9 populations using 8 InDel markers. Results indicated a relatively high level of within-population genetic diversity (He = 0.35) and limited among-population differentiation (FPT = 0.20) for this predominantly self-pollinating grass. UPGMA cluster analyses, PCoA and Bayesian clustering supported the demarcation of the populations into 3 groups that were not correlated with location or altitude, suggesting a loose genetic affinity of B. hybridum populations in relation to their geographical locations, and no obvious genetic structure among populations across the study area. This pattern was associated with a considerable amount of an asymmetric gene flow between populations. Overall, the obtained results suggest that the long-distance seed-dispersal is the most important factor in shaping the spatial genetic structure of B. hybridum in Tunisia. They also provide key guidelines for on-going and future work including breeding programs and genome-wide association studies.